2018
DOI: 10.3389/fonc.2018.00543
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Patients With Prostate Cancer Initiating GnRH Agonists/Antagonists Therapy Using a German Claims Database: Epidemiological and Patient Outcomes

Abstract: Objective: The objective of this study was to obtain real-world information on gonadotropin-releasing hormone agonist/antagonist (GnRHa) therapy in patients with advanced prostate cancer (PCa).Materials and methods: Anonymized, routine healthcare claims data from approx. 75 German statutory health insurance funds from 2010–2015 (n = 4,205,227) were analyzed. Patients had an enrolment of 1 year before GnRHa, 1 index quarter of initial GnRHa prescription and ≥2 years of follow-up.Results: In total, 2,382 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
0
18
0
2
Order By: Relevance
“…Most but not all real-world observational data suggest that treatment with GnRH antagonists is associated with fewer cardiovascular event rates than treatment with GnRH agonists [ 35 ]. Real-world observational data from 2382 patients with advanced prostate cancer from a German claims database showed no significant differences in the incidence of CVD or diabetes between GnRH agonists or antagonists overall, although there was a significant increase in hypertension in patients receiving a GnRH agonist (16.4%) compared with those receiving a GnRH antagonist (6.9%, p = 0.022) [ 42 ]. Similarly, data from 35,118 ADT users identified from a French population-based claims reimbursement database demonstrated no significant association between GnRH antagonists and CV risk [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most but not all real-world observational data suggest that treatment with GnRH antagonists is associated with fewer cardiovascular event rates than treatment with GnRH agonists [ 35 ]. Real-world observational data from 2382 patients with advanced prostate cancer from a German claims database showed no significant differences in the incidence of CVD or diabetes between GnRH agonists or antagonists overall, although there was a significant increase in hypertension in patients receiving a GnRH agonist (16.4%) compared with those receiving a GnRH antagonist (6.9%, p = 0.022) [ 42 ]. Similarly, data from 35,118 ADT users identified from a French population-based claims reimbursement database demonstrated no significant association between GnRH antagonists and CV risk [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation was the small sample size of degarelix-treated patients, which prevented subgroup analysis of individual risk factors. The small sample size is common to other retrospective analyses of degarelix, with the low number of patients taking degarelix possibly due to clinicians favouring GnRH agonists as first-line treatments [42,47]. Further, events of hypertension, stroke, and CV death were not included in the analysis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Similar to the present study, toxicity was reported in the German study in 9% of patients, and the majority were not considered serious. Of note, this LHRH agonist was found to be the most frequently used form of medical castration in another study from Germany, in this case based on a claims database (15).…”
Section: Discussionmentioning
confidence: 78%
“…Die Ergebnisse werden im Folgenden in 4 Abschnitten dargestellt: 1) Patientencharakteristika, 2) Komorbidität und Mortalität, 3) Therapiemuster sowie 4) Hospitalisierung. Die ersten Ergebnisse mit Fokus auf den Krankheitsverlauf sind in einer kürzlich erschienenen Studie unserer Arbeitsgruppe ausführlicher beschrieben [18]. Bei der vorliegenden Studie mit Schwerpunkt Gesundheitsökonomie liegt der Fokus hingegen auf den Therapie-und Verschreibungsmodalitäten sowie den Krankenhaustagen und -kosten.…”
Section: Conclusion: This Comparative Retrospective Analysis Pro-unclassified